2018
DOI: 10.3389/fpsyg.2018.01984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Auditory Attention on Temporal and Spectral Resolution

Abstract: Previous research in the visual domain suggests that exogenous attention in form of peripheral cueing increases spatial but lowers temporal resolution. It is unclear whether this effect transfers to other sensory modalities. Here, we tested the effects of exogenous attention on temporal and spectral resolution in the auditory domain. Eighteen young, normal-hearing adults were tested in both gap and frequency change detection tasks with exogenous cuing. Benefits of valid cuing were only present in the gap detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…An important question is whether temporal integration windows reflect a fixed property of the cortical hierarchy or whether they are shaped by attention and behavioral demands 73 . In our study, we did not give subjects a formal task because our goal was to measure integration windows during natural listening without any particular goal or attentional focus.…”
Section: Discussionmentioning
confidence: 99%
“…An important question is whether temporal integration windows reflect a fixed property of the cortical hierarchy or whether they are shaped by attention and behavioral demands 73 . In our study, we did not give subjects a formal task because our goal was to measure integration windows during natural listening without any particular goal or attentional focus.…”
Section: Discussionmentioning
confidence: 99%
“…As stimuli, 0 to 3 silenced gaps are embedded within 6-second white noise. There are ten different gap durations (2,3,4,5,6,8,10,12,15, and 20 ms), and the duration or location of the gaps within the noise is pseudorandomized. As each gap appears six times in each track, a total of 60 gaps were presented.…”
Section: Test Of Auditory Temporal Resolution (Gaps-in-noise Test)mentioning
confidence: 99%
“…The gap detection threshold is known to depend on a variety of stimulus characteristics such as stimulus level, stimulus bandwidth, modulation features, spectral and temporal complexity, and uncertainty [1]. Several evidences suggest that gap detection performance is related to cognitive demand or attentional resources [4][5]. For example, Leung, et al [4] measured auditory event-related potentials during active and passive listening and found that gap detection performance was associated with attentional processing, possibly related to divided attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation